MANAJEMEN KURIKULUM, ASESMEN, DAN MUTU PEMBELAJARAN DI SEKOLAH INDONESIA: A SYSTEMATIC REVIEW - Okta Iwan Setiawan; Agus Pahrudin; Sri Rahmi (STKIP Pesisir Selatan, 2026)
Objective: This study aims to systematically synthesize the relationship between curriculum management, assessment, and learning quality in Indonesian schools. This research employed a systematic literature review method by following the PRISMA 2020 framework, which includes the stages of identification, screening, eligibility assessment, and inclusion of articles. The data were obtained from scholarly articles relevant to curriculum management, learning assessment, the implementation of the Merdeka Curriculum, and learning quality in Indonesian school contexts. Through the selection process, 42 articles met the inclusion criteria and were analyzed using thematic synthesis. The findings reveal that learning quality is not determined merely by the availability of curriculum documents, but by the coherence between curriculum planning, instructional implementation, diagnostic and formative assessment, academic supervision, and a reflective school culture. The results also show that assessment has a strategic function as an instrument for identifying students’ learning needs, providing feedback, adjusting instructional strategies, and improving the learning process continuously. However, the implementation of curriculum management and assessment in Indonesian schools still faces several challenges, including uneven teacher literacy in curriculum and assessment, the dominance of administrative orientation, limited academic supervision, teachers’ workload, and disparities in school resources. This study concludes that curriculum management, assessment, and learning quality should be understood.